Simple and efficient one-pot, three-component, solvent-free synthesis of beta-enaminones via sonogashira coupling-Michael addition sequences - Palimkar, Sanjay S.; More, Vijaykumar S.; Srinivasan, Kumar V. (Synthetic Communications, 2008)
A simple, efficient, and environmentally friendly one-pot, three-component synthesis of beta-enaminones via Sonogashira coupling-Michael addition sequences under solvent-free conditions has been reported. Also the synthesis of beta-enaminones has been achieved in high yields by the direct reaction of amines with ynones under solvent-free conditions.
Keywords: Alkynes; beta-enaminones; coupling; Michael additions; solvent free; ynones